Pengaruh Lamanya Kebiasaan Menggunakan Pantyliner Terhadap Kejadian Fluor Albus Patologis - Rahmasari, Halisa; Yuniati, Lisa; Irwan, Andi Alamanda; Dewi, Anna Sari; Abdi, Dian Amelia (Indonesian Journal of Health, 2023)
Fluor albus is the term for the symptoms of fluid discharge from the genitalia of a woman who is not blood. To use of Pantyliner with long duration that is a risk of pathological fluorine. The impact to use of pantyliner used daily turns out to cause bacterial or fungal infections in the femininity area. This happens because the Pantyliner makes the femininity area become increasingly humid. Too long using pantyliner is harmful to the health of female organs. The pantyliner that is not replaced within a few hours will be moist and become a medium of fungal or bacterial growth. The purpose of the study was to know the long relationship of habit using a pantyliner to the pathologic fluorine incident on the cohorts of force 2017 and 2018. The research design used in this study is observational analytic with cross sectional design. Sampling techniques in this research are Puposive Sampling. The study used the Chi-Square test.